2018
DOI: 10.5194/acp-18-9075-2018
|View full text |Cite
|
Sign up to set email alerts
|

Production and transport mechanisms of NO in the polar upper mesosphere and lower thermosphere in observations and models

Abstract: Abstract. A reservoir of nitric oxide (NO) in the lower thermosphere efficiently cools the atmosphere after periods of enhanced geomagnetic activity. Transport from this reservoir to the stratosphere within the winter polar vortex allows NO to deplete ozone levels and thereby affect the middle atmospheric heat budget. As more climate models resolve the mesosphere and lower thermosphere (MLT) region, the need for an improved representation of NO-related processes increases. This work presents a detailed compari… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
35
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(40 citation statements)
references
References 54 publications
3
35
0
Order By: Relevance
“…Recent studies have shown that either constraining the model up to 90 km or assimilating mesospheric data improves the representation of the EPP IE Sassi et al, 2018;Siskind et al, 2015). In the Antarctic, Hendrickx et al (2018) show EPP-NO x underestimates despite MLT descent rates in WACCM that agree with observations. This result bolsters the argument that missing NO production is responsible for the model NO underestimates, although they also note that the model could have too much NO destruction or too strong horizontal diffusion.…”
Section: Introductionmentioning
confidence: 81%
“…Recent studies have shown that either constraining the model up to 90 km or assimilating mesospheric data improves the representation of the EPP IE Sassi et al, 2018;Siskind et al, 2015). In the Antarctic, Hendrickx et al (2018) show EPP-NO x underestimates despite MLT descent rates in WACCM that agree with observations. This result bolsters the argument that missing NO production is responsible for the model NO underestimates, although they also note that the model could have too much NO destruction or too strong horizontal diffusion.…”
Section: Introductionmentioning
confidence: 81%
“…The standard TIME-GCM model uses a value for Reaction (R2) of 7 × 10 −13 cm 3 s −1 from Fell et al (1990). As discussed by Yonker (2013), Herron (1999) Figure 3 compares the diurnal NO variation between the driven and nudged models. It shows that both models have peak NO densities in the lower thermosphere of just over 10 8 cm −3 .…”
Section: Overview Of Approachmentioning
confidence: 92%
“…inferred a temperature dependence of this rate that appears to neglect the Fell et al(1990) reference. Instead, relying upon older studies,Herron (1999) recommends a room temperature value which is about double the room temperature measurement of Fell et al(1990). Thus in doubling the rate coefficient R2 we are essentially, as an academic exercise, using Herron's somewhat arbitrary room temperature value in lieu of Fell et al's (1990) measurement.…”
mentioning
confidence: 99%
“…Chemistry-climate models struggle to simulate the NO amounts and distributions in the mesosphere and lower thermosphere (see, for example, Funke et al, 2017;Randall et al, 2015;Orsolini et al, 2017;Hendrickx et al, 2018). To remedy the situation, some models constrain the NO content at their top layer through observation-based parametrizations.…”
mentioning
confidence: 99%
“…The dissociation energy of N 2 into ground state atoms N( 4 S) is about 9.8 eV (λ ≈ 127 nm) (Hendrie, 1954;Frost et al, 1956;Heays et al, 2017). This energy together with the excitation energy to N( 2 D) is denoted by hν in Reaction (R1) and can be provided by a number of sources, most notably by auroral or photoelectrons as well as by soft solar X-rays.…”
mentioning
confidence: 99%